2013
DOI: 10.1038/nature12518
|View full text |Cite
|
Sign up to set email alerts
|

Social reward requires coordinated activity of nucleus accumbens oxytocin and serotonin

Abstract: Social behaviors in species as diverse as honey bees and humans promote group survival but often come at some cost to the individual. Although reinforcement of adaptive social interactions is ostensibly required for the evolutionary persistence of these behaviors, the neural mechanisms by which social reward is encoded by the brain are largely unknown. Here we demonstrate that in mice oxytocin (OT) acts as a social reinforcement signal within the nucleus accumbens (NAc) core, where it elicits a presynaptically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
899
4
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 994 publications
(932 citation statements)
references
References 47 publications
(74 reference statements)
25
899
4
4
Order By: Relevance
“…Indeed, OT has been shown to increase spike output 89-91 and facilitate synaptic long-term potentiation 92-94 and our data suggest an intrinsic mechanism that may underlie shifts in synaptic efficacy and excitatory/inhibitory balance found in brain regions where OT is critical for myriad social behaviors 67,74,90,95 . Intrinsic properties are shaped by ion channels.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Indeed, OT has been shown to increase spike output 89-91 and facilitate synaptic long-term potentiation 92-94 and our data suggest an intrinsic mechanism that may underlie shifts in synaptic efficacy and excitatory/inhibitory balance found in brain regions where OT is critical for myriad social behaviors 67,74,90,95 . Intrinsic properties are shaped by ion channels.…”
Section: Discussionmentioning
confidence: 71%
“…After achieving a whole-cell configuration, baseline recordings were made in aCSF until 10 minutes of stable baseline were observed, at which point 500 nM oxytocin citrate was added to the bath. The dose of 500 nM was selected after a pilot study using a range of doses from 50nM to µ1M, the largest dose reported 95 . Because OT has high affinity for the Vasopressin 1A receptor (V1a), experiments typically isolate effects of OT to the OTR by using synthetic OTR agonists or a cocktail of OT and V1a antagonists.…”
Section: Insular Cortex Slicesmentioning
confidence: 99%
“…The NAC has been heavily implicated in stress responses, mood disorders, and processing natural rewards 2,5,[11][12][13][16][17][18][19][20][21] . Moreover, pathophysiological dysfunction of the NAcc in response to various stressors has been implicated in anhedonia and reward conditioning [18][19][20][21] .…”
mentioning
confidence: 99%
“…Moreover, the receptors and their endogenous lipid-derived ligands, anandamide and 2-arachidonoyl-sn-glycerol (2-AG) (8), have been implicated in the control of social play (9) and social anxiety (10,11), two crucial aspects of the social experience. Another essential facet of social behavior, the adaptive reinforcement of interactions among members of a group (i.e., the reward of being social), requires the oxytocin-dependent induction of long-term synaptic plasticity at excitatory synapses of the nucleus accumbens (NAc) (12), a key region in the brain reward circuit. Because the endocannabinoid system regulates the reinforcement of various natural stimuli (13) as well as NAc neurotransmission (14), in the present study we tested the hypothesis that this signaling complex might cooperate with oxytocin to control social reward.…”
mentioning
confidence: 99%